2022
DOI: 10.1227/ons.0000000000000442
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Artery Stenting Using the Walrus Balloon Guide Catheter With Flow Reversal for Proximal Embolic Protection: Technical Description and Single-Center Case Series

Abstract: BACKGROUND: The use of modern transfemoral balloon guide catheters (BGC) for flow reversal during carotid artery stenting is scarcely described in the literature but represents a promising and efficient technique for embolic protection. OBJECTIVE: To describe a flow-reversal technique using the Walrus BGC (Q'Apel Medical Inc.) and report our center's experience. METHODS: We performed a retrospective analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Hence, in the future, findings from this study may also inform potential differences between the similarly sized new generation large bore BGCs compared to the conventional (non-balloon) guide catheters. The results of this study could also potentially be applicable to other neurointerventional procedures where proximal flow arrest may be considered, such as in carotid artery stenting for symptomatic carotid stenosis (30).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Hence, in the future, findings from this study may also inform potential differences between the similarly sized new generation large bore BGCs compared to the conventional (non-balloon) guide catheters. The results of this study could also potentially be applicable to other neurointerventional procedures where proximal flow arrest may be considered, such as in carotid artery stenting for symptomatic carotid stenosis (30).…”
Section: Discussionmentioning
confidence: 92%
“…The results of this study could also potentially be applicable to other neurointerventional procedures where proximal flow arrest may be considered, such as in carotid artery stenting for symptomatic carotid stenosis. 30…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14) Larger GCs are also frequently employed in carotid artery stenting procedures. 15,16) While using large GCs raises safety concerns due to the small size of the radial artery, 3) Hanaoka et al 7) reported a RAO rate of 1.5% in their study of TRA-NET using a 6-F guide sheath (which has an outer diameter equivalent to that of a sheathless 8-F GC). This rate aligns with findings from previous studies and our study.…”
Section: Journal Of Neuroendovascular Therapymentioning
confidence: 99%
“…In their study, they found no difference in outcome between CEA and CAS. This may reflect the advancement of the endovascular device including stroke protection filter and flowreversal technique (20,21). We need to keep in mind that compared to the past now that various endovascular devices are developed, we need to update the result from past studies ( 22).…”
mentioning
confidence: 99%